EFFECTS OF SULFUR AND UREASE COATED CONTROLLED RELEASE UREA ON DRY MATTER YIELD, N UPTAKE AND GRAIN QUALITY OF RICE - A. Z. Khan; B. Ali; M. Afzal; S. Wahab; S. K. Khalil; N. Amin; Q. Ping; T. Qiaojing; W. Zhou (Journal of Animal and Plant Sciences, 2015)
The application of urea fertilizer has always been associated with heavy N losses therefore, improving its efficiency is critical to minimize economic and environmental losses associated with its application. One possible approach to improve the nitrogen losses from the surface applied urea is to coat it with sulfur, urease inhibitor (agrotain) and other biodegradable materials. A pot experiment was carried out using two different textured: silt loam and clay loam soil to- assess the effect of sulfur and urease inhibitor (agrotain) on dry matter yield, N uptake and grain quality at the green house of the Zhejiang University, Hangzhou, China during 2011-12. The experiment consisted of treatments arranged in a completely randomized block design (CRD) with 3 replications. Urea coated with sulfur and urease inhibitor (agrotain) was applied at 60 kg N ha-1 in 2 splits. The results showed that sulfur and urease inhibitor (agrotain) coated urea significantly increased the dry matter yield, N uptake and grain quality of rice cultivars over  granular urea (GU) and control treatment applied split, particularly in silty loam soil than clay loam soil.The N release was more pronounced in silty loam (SL) soil as compared to clay loam (CL) soil where, the effect of the inhibitors was less evident. Japonica cultivar (xinshui 123) showed its superiority over indica cultivar (9311) in all the studied parameters. It is concluded from these results that controlled released urea fertilizer improved dry matter yield by 55-68% ha-1, enhanced N uptake upto 39.4% and grain protein percentage from 5.8% -14.9% as compared to granular urea and control treatment. The improvement in rice dry matter yield and grain quality caused by sulfur and urease inhibitor (agrotain) coating may have been due to increased N use efficiency with split application in these two different textured soils.
Keywords: rice; sulfur; slow release urea; N uptake and grain quality